ANALYSiS OF EPiZOOTOLOGiCAL AND EPiDEMiOLOGiCAL ANTHRAX SiTUATiON iN 2000-2011 AND PROGNOSiS FOR 2012-2015 - Z. F. Dugarzhapova; M. V. Chesnokova; A. V. Rodzikovsky (Acta Biomedica Scientifica, 2012)
Epizootological and epidemiological anthrax situation in Siberia in 2000—2011 was analyzed. On the basis of the situation evaluation and. geographical demarcation of Siberia territory the anthrax morbidity was prognosed